What We Know and Dont Know on Sars-Cov-2 and Covid-19 [Lo Que Sabemos y No Sabemos Sobre Sars-Cov-2 y Covid-19] - Bachelet-Norelli, V; Silva-Ayarza, I (Medwave Estudios Ltda, 2021)
Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus discovered in December 2019 in Wuhan, China, has had an enormous impact on public health worldwide due to its rapid spread and pandemic behavior, challenges in its control and mitigation, and few therapeutic alternatives. In this review, we summarize the pathophysiological mechanisms, clinical presentation, and diagnostic techniques. In addition, the main lineages and the different strategies for disease prevention are reviewed, with emphasis on the development of vaccines and their different platforms. Finally, some of the currently available therapeutic strategies are summarized. Throughout the article, we point out the current knowns and unknowns at the time of writing this article. © 2021, Medwave Estudios Ltda. All rights reserved.